The induction of adventitious roots in Rosal (Gardenia jasminoides) cuttings using balete (Ficus elastica) root extract as a natural plant root growth inducer. - Recabar, Oscar (2010.)
The study on the use of different levels of concentration of balete root extracts on Gardenia jasminoides cuttings was conducted at the laboratory of the Division of Biological Sciences, University of the Philippines Visayas, Miag-ao, Iloilo. The study aimed to find out if a significant difference among the treatments in terms of length (mm) and number of roots produced. The cuttings were soaked in different balete root extract levels of concentration and were replicated five times. Treatment A ( 1000 percent ), Treatment B ( 50 percent ), Treatment C ( 25 percent ), Treatment D ( 12.5 percent ), Treatment E negative ( 100 percent distilled water ) and Treatment F positive ( 100 percent ANAA ). After 28 days of soaking, the length and number of roots developed were measured and interpreted. ANOVA in RCBD revealed that the soaking of cuttings in different balete root concentrations had a highly significant effect on the length of roots developed but did not significantly influence the number of roots developed. Furthermore, DMRT revealed that the most effective among treatments in lengthening roots was Treatment D (12.5 percent balete root extract). Balete root extract showed promising result and could therfore be a feasible substitute to a commercial root growth inducer. This is one way of minimizing the use of chemical substances that could harm the environment.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Flowers -- Rosal; Gardenia jasminoides; Balete; Ficus elastica